Studies on noise generation in workplaces of locomotive crews from acoustic radiation effects of the internal sources - Sergey F. Podust (Advanced Engineering Research)
The research objective is to study regularities of the noise spectra development at the working sites of locomotive brigades created by the sound radiation of the internal noise sources, and the conformity octave sound pressure levels to the sanitary standards. The investigation results are given. The measurements are carried out on freight and passenger locomotives by the noise and vibration analyzer “Assistant Total+”, accuracy rating 1, with preamplifier PU-01 and MIC capsule МК233 with a frequency measurement range from 2 up to 40,000 Hz. The experimental studies have shown that almost all the internal noise sources produce the sound pressure level increase above the maximum permissible values.